Neuroscientific Principles in Labour Adaptation of People with Musculoskeletal Disorders - Sarancha, Iryna; Maksymchuk, Borys; Gordiichuk, Galyna; Berbets, Tetiana; Berbets, Vitalii; Chepurna, Liudmyla; Golub, Volodymyr; Chernichenko, Liudmyla; Behas, Liudmyla; Roienko, Svitlana; Bezliudna, Natalia; Rasskazova, Olha; et al. (My University, 2021)
The article proves that the socialization of adults and children with musculoskeletal disorders (MSDs) is closely related to development, education, rehabilitation and includes the following neuropsychological aspects: social adaptation, labour adaptation, assessment of prospects for one’s adult life and creation of a non-discriminatory environment in society. Besides, the article shows how the photography club implements such goals, as well as evaluates the effectiveness of its activities. The educational aim of the photography club was to familiarize persons with MSDs with the basic types of working with digital photography and basic computer programmes that enable processing of digital information; to develop their knowledge about the photography and design business, computer skills and independent work skills. The experimental group (EG) consists of 40 leavers (18 males and 22 females) from the Vinnytsia Centre for Social Rehabilitation of Children with Special Needs “Promin”, who were diagnosed with cerebral palsy and six leavers with mild mental disorders. The age requirement for EG is 14-19 years old. The control group (CG) consists of 40 persons diagnosed with CP and seven persons with mild mental disorders (23 males and 17 females). The respondents managed to study different types of shooting: portraits, landscapes, group and individual photography. The photography club used different methods: verbal methods (mini-lectures, stories, explanations, conversations); practical methods (computer exercises, independent work, role-playing games), as well as paid considerable attention to the psychological correction of persons with MSDs. Unfortunately, most options of the respondents for employment are rather passive. Therefore, it is necessary to prepare persons with MSDs for competition in the labour market through psychological training and counselling. It is also crucial to promptly inform them about the dynamics of the labour market. The international relevance of the article lies in an attempt to adjust available electronic and software technologies to labour adaptation of people with MSDs and consider neurophysiological patterns of such a process.
Neuroscientific Principles in Labour Adaptation of People with Musculoskeletal Disorders / I. Sarancha, B. Maksymchuk, G. Gordiichuk, T. Berbets, V. Berbets, L. Chepurna, V. Golub, L. Chernichenko, L. Behas, S. Roienko, N. Bezliudna, O. Rassskazova, I. Maksymchuk // BRAIN. Broad Research in Artificial Intelligence and Neuroscience, 2021. – Vol. 12. – Issue 4 . – P. 206–223.
Keywords: соціальна адаптованість, соціалізація, церебральний параліч, комп'ютерна грамотність, почуття, вплив на розвиток; social adaptability, socialization, cerebral palsy, computer literacy, feelings, developmental impact